Compressive relaxation properties of human meniscus increase under combined traction and compression. - Peña Trabalón, Alejandro; de Roy, Luisa; Pérez-Blanca, Ana; Prado-Novoa, María; Seitz, Andreas Martin (My University, 2024)
Physiologically, the meniscal horns are subjected to a complex loading combination of compressive axial forces and internal circumferential tensile loading. However, while the compressive properties of human menisci have been extensively studied, the impact of tensile loading on the compressive properties is unknown. Therefore, the aim of this study was to analyze the changes in the compressive relaxation properties of the meniscal horn under combined axial compression and circumferential traction.
Keywords: Biomecánica; Menisco - Investigación; Sutured meniscus; Compressive properties; Indentation; Physiological loads; Human